If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 34z = 36z + -7 Reorder the terms: 34z = -7 + 36z Solving 34z = -7 + 36z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-36z' to each side of the equation. 34z + -36z = -7 + 36z + -36z Combine like terms: 34z + -36z = -2z -2z = -7 + 36z + -36z Combine like terms: 36z + -36z = 0 -2z = -7 + 0 -2z = -7 Divide each side by '-2'. z = 3.5 Simplifying z = 3.5
| x^(1/2)-8x^(1/4)-15 | | 2x(x+3)-6=4x-5 | | 0.5x+0.15(100)=0.4(x+100) | | -15=2x-7 | | 6-11x-p^2=0 | | 7x-4=2+1+9x-5 | | 4r+s-2t= | | 3(x+2)=x-4 | | 3(x+2)=x-4 | | 14=b+23 | | (5C-7)(3)= | | 0.0022b=0 | | 47=4(x+6)-(7x+1) | | 4+6x=2x | | 4r-4s+4t= | | 6x-3(2y-3)=y-2(4x-1) | | (x-6)(2x+2)= | | 23=-1-6x | | 2+4x=x | | 7w+3w^2+2=3w^2+9 | | -5x+7x-8x=0 | | 2(3x+5)=2x+42 | | -5x-5y+5z= | | (3/5)x=(4/3) | | 4(7z+9)=-24+5z | | x(x+7)-4=7x+32 | | 7=2+9.3 | | x+1/x=12/(x-1) | | 5x/3+10=0 | | -8(v+3)+3v+5=7v+8 | | 21/6j_51/5 | | [n-4]=13 |